Scrapie pathology and its relationship to infectivity following intraocular infection - Scott, Janet Reid (The University of Edinburgh, 1991)
Different strains of scrapie can be distinguished by the characteristic pattern of vacuolar degeneration which develops in the murine brain, and by the length of the incubation period. The causal agent has not been identified, and the presence of infection within tissues can only be demonstrated by bioassay. In this study, the intraocular route of infection was exploited to examine the development of the pathology produced by six different scrapie strains, and to compare the pattern of lesion targeting within this well-studied anatomical system with the spread of infectivity. Scrapie incubation period is controlled by the murine Sine gene, which has two alleles; lesion development was recorded in both mouse genotypes following infection with several of the scrapie strains. The pattern of lesion development was found to correspond closely with the neuroanatomical pathways from retina via the optic nerve to the visual projection areas in the brain. The earliest lesions in all models appeared in the second half of the incubation period, and were confined to the visual projection areas on the contralateral side of the brain to the injected eye (there is almost complete decussation at the murine chiasma). The first lesions were seen either in the superior colliculus or the dorsal lateral geniculate nucleus, depending on the scrapie model; these are both major projections of the optic nerve. The pattern of subsequent lesions within the visual system also varied, gradually affecting both sides of the brain, until in the terminal mouse, the lesions were usually similar to those resulting from an intracerebral route of infection.

The spread of infectivity following intraocular infection 2 was studied by bioassay of tissues throughout the incubation period. The rise in infectivity levels of ME7 scrapie correlated closely with the sequence of lesion targeting, although infectivity wsls detected much earlier in the incubation period. Several questions relating to the sites of replication, and the spread of infectivity were investigated by bioassay of appropriate tissues. The lower levels of infectivity in retinas from mice with an inherited retinal defect, compared to normal mice, suggested that the photoreceptor cells support scrapie replication; these cells are destroyed following infection with 79A scrapie. The Sine gene was shown to delay replication in the single neuronal relay to the superior colliculus by 50 - 60 days, suggesting that this gene acts on the transport and/or replication of infectivity. High levels of infectivity were found in the spleen following intraocular infection, indicating that inoculum escaping from the eye initiates replication in the lymphoreticular system. Similarly, disease could also be produced by conjunctival instillation of inoculum with no evidence of contralateral targeting of lesions.

The way in which infectivity spreads within neurons was studied using serial enucleation after infection, alteration of retinal ganglion cell number in mice, and attempted modification of initial infection. Following serial enucleation of the infected eye, the lesion pattern and incubation periods with ME7 scrapie indicated that infectivity spread at a similar rate to that of slow axoplasmic transport. Preliminary results with two other scrapie strains show similar timings, suggesting that spread within axons is a passive process associated with normal cellular metabolism. This means that Sine gene control is exerted through its effect on replication rather than transport.